2014
DOI: 10.1167/iovs.14-15435
|View full text |Cite
|
Sign up to set email alerts
|

Models of Glaucomatous Visual Field Loss

Abstract: While the logistic model best fit glaucomatous VF behavior over a long time period, the exponential model provided the best average predictions. A multiple-model approach for VF predictions was associated with a greater prediction error than with the best-performing single-model approach. A model's goodness of fit is not indicative of its predictive ability for measurements of glaucomatous VFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 16 publications
3
34
1
Order By: Relevance
“…Chen et al compared the ability of pointwise linear, exponential, and logistic functions, and combinations of functions, to model the longitudinal behavior of visual field series and predict future visual field loss in patients with glaucoma. They found that while the logistic model best fit glaucomatous visual field behavior over a long time period, the exponential model provided the best average predictions (Chen et al, 2014). Azarbod et al investigated a pointwise exponential regression model to calculate average rates of faster and slower deteriorating visual field components, as well the entire visual field.…”
Section: Nature Of Glaucomatous Visual Field Progressionmentioning
confidence: 99%
“…Chen et al compared the ability of pointwise linear, exponential, and logistic functions, and combinations of functions, to model the longitudinal behavior of visual field series and predict future visual field loss in patients with glaucoma. They found that while the logistic model best fit glaucomatous visual field behavior over a long time period, the exponential model provided the best average predictions (Chen et al, 2014). Azarbod et al investigated a pointwise exponential regression model to calculate average rates of faster and slower deteriorating visual field components, as well the entire visual field.…”
Section: Nature Of Glaucomatous Visual Field Progressionmentioning
confidence: 99%
“…Simple linear regression estimates may result in predictions of negative values that are incompatible with the measurements, as well as predictions of improving sensitivities that are not universally accepted to occur after a learning period (Gardiner et al, 2008;Musch et al, 2014). Censoring the estimates of pointwise analysis by not allowing negative sensitivity values or improving sensitivities may greatly improve predictions (Chen et al, 2014).…”
Section: Pointwise Trend Analysismentioning
confidence: 99%
“…Several regression models have been explored to perform trend-based analysis, including simple linear regression, censored linear regression, exponential, robust, quadratic, and logistic (Bryan et al, 2013;Caprioli et al, 2011;Chen et al, 2014;Pathak et al, 2013). An exponential model could better describe the loss of visual field sensitivity over a longer period of time, but a linear model may be appropriate for shorter periods of a few years .…”
Section: Pointwise Trend Analysismentioning
confidence: 99%
“…Furthermore, the method appears not to be significantly affected by the level of IOP or progression rate. However, despite a significant reduction in prediction error, the magnitude of this improvement is small relative to previous novel regression models that use only VF data345678910. One of the possible reasons for such a small improvement is that IOP fluctuates in the short and long term21 and measuring IOP at the clinic in approximately three month intervals is too infrequent to observe the true trend in IOP.…”
Section: Discussionmentioning
confidence: 92%
“…We have reported several alternative approaches to improve the prediction accuracy of VF progression, such as robust regression3, least absolute shrinkage and selection operator (Lasso) regression4, cluster-wise regression56, and also variational Bayesian linear regression7. In addition, many other successful efforts have been reported from other researchers891011121314, nonetheless ordinary OLSLR is still very frequently used at the clinical setting. One thing that all these approaches have in common is that VF progression is predicted using only VF measurements; however, other parameters are routinely captured in the clinic which may be useful to supplement any model of VF progression.…”
mentioning
confidence: 99%